Extramedullary plasmacytoma in the frontal scalp - Antolinez Ayala, Víctor Enrique; Villamizar Conde, Damaris Jhojana; Torres Parra, Deisy Yurani (Revista Argentina de Neurocirugía, 2024)
Background. Plasmacytoma is a rare plasma cell dyscrasia of unknown etiology. Extramedullary plasmacytoma (EMP) is a neoplasia generally located in sites such as bone or soft tissue and which in turn exert a mass effect and/or pain. Radiotherapy and surgery have been the primary treatment.Objectives. To describe a clinical case of atypical presentation and to characterize the manifestations of the disease.Case description. A 48-year-old female patient with a rapid growth in the last 18 months of a frontal mass that had been evolving for 4 years. It was slightly hard to the touch, painful, and non-mobile. No neurological symptoms associated. An initial MRI was performed followed by a CT scan, which showed tumor growth, so it was decided to perform surgery.Surgery. Craniotomy and tumor resection were performed. The pathology reported extramedullary plasmacytoma. After one month, the patient had improved favorably.Conclusion. It is important to consider the different presentations of EMP to make an appropriate diagnosis and treatment, obtaining the best possible prognosis.
Keywords: Biomarkers; Extracranial mass; Plasmacytoma; Scalp